PERBANDINGAN PENENTUAN BILANGAN IODIN PALM OIL DENGAN DAN TANPA KATALIS NATRIUM ASETAT - Elizarni, Elizarni; Nurlan, Nurlan (Politeknik ATI Padang, 2017)
Iodine value is the number of grams of Iodide absorbed by 100 grams of oil, is one of the quality standards of palm oil. Determination of Iodine value is done by titration of iodometri (Wi's method) with or without Sodium Acetate solution catalyst. The addition of a catalyst for the acceleration of the reaction so that the analysis time is more efficient. The test sample consisted of RBDPO, RBDPS, Cooking Oil IV 56, Cooking Oil IV 57, Cooking Oil IV 58, Cooking Oil IV 59, Cooking Oil IV 60. Results of Iodine Numeral analysis with and without catalyst for RBDPO samples were 52.24 and 52.35, RBDPS samples were 33.18 and 33.24, Cooking Oil IV 56 samples were 56.02 and 56.09, Cooking Oil IV 57 samples were 57.28 and 57.34, Cooking Oil IV 58 samples of 58.00 and 58.10, Cooking Oil sample 59 that is 59.17 and 59.21, sample of Cooking Oil IV 60 that is 60.42 and 60.46. The test results of each sample showed no significant differences with standard iodine numbers. T Test is performed for determination of data acquisition of Iodine number acceptable or not. T test result of Iodine number using catalyst and without catalyst of RBDPO sample obtained t0<ttable that is 1.947<2.015 and sample RBDPS 1.924<2.015 so that method obtained can be accepted (valid).